The Genus Bilabrella Lindl. (Orchidaceae, Habenariinae): General Characteristic and Research History of The Genus - Kras, Marta; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2015)
The genus Bilabrella (Habenarinae, Orchidaceae) was described by Lindley in 1834, but within next years, different authors incorporated it as the section of the genus Habenaria Willd. From 2003, Szlachetko and Kras stated that there were no grounds for distinguishing the sections Bilabrellae and Replicatae. They restored the genus Bilabrella, transfering to it 93 species from the section Replicatae and four species new to science were described. The poor condition of the old plant materials, the lack of some type specimens for many species described by Schlechter and problems with a series of transitional forms between some species are only few reasons, why the revision of the genus has not been published so far. Bilabrella comprises orchids found in Sub-Saharan Africa, Madagascar and neighbouring islands. Bilabrella differs from other Habenariinae in its unique combination of features